TWO-PHASE FLOW STRUCTURE IDENTIFICATION BASED ON FUZZY ASSESMENT OF 3D TOMOGRAPHICAL IMAGING - Jaworski, Tomasz; Fiderek, Paweł; Wajman, Radosław; Banasiak, Robert (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
The following paper presents results of research on automated two-phase flow pattern identification, which is based on a fuzzy assessment of registered spatial images. Such images are obtained from 3D tomography reconstruction algorithms and for each a set of fuzzy-based features is calculated. Finally, acquired features are used to classify obtained image to one of flow regime structures.